The Relationship Between Digital Literacy and Learning Outcomes in Biology Learning for Students - Nur Hafiza; Hanum Mukti Rahayu; Adi Pasah Kahar (Jurnal Penelitian Pendidikan IPA, 2022)
The study aims to determine the relationship between digital literacy and the learning results on the biology of class vii for the 12th country school class vii. This type of research is a quantitative study with a correlational method. The population in this study is class vii in the 12 countries' middle schools. The samples used in this study number 88 students. Research instruments using tankettes. The data analysis technique used is by using a product-moment correlation. Studies show the class vii c, d, e, and f's digital literacy of class vii c, d, e, and f get an average of 60.77 present in the moderate category. In contrast, the results of the student biology study of students get an average of 68.02 gifts in the intermediate class. Product correlation analysis between x variables and y variables show that r recount (0.290) > t-table (1.987) so that there is a link between digital literacy and the study of the biological student vii class 12 countries